Genetic Diversity of Wild and Cultivated Muscadine Grapes (Vitis rotundifolia Michx.) - Buck, Kenneth; Worthington, Margaret (Frontiers in Plant Science, 2022)
The muscadine (Vitis rotundifolia syn. Muscadinia rotundifolia) is an American grape species native to the southeastern United States that has been cultivated for centuries. Muscadines are one of three grape species in subgenus Muscadinia with a chromosome number of 2n=40 (V. rotundifolia, V. munsoniana, and V. popenoei), making them genetically distinct from the European wine and table grape (Vitis vinifera) and other species in subgenus Euvitis. Crop improvement efforts have been continuous since the late 19th century, yet the germplasm that served as the foundation for early muscadine breeding efforts was sourced from a relatively small portion of their native range, mostly in the coastal plains of North Carolina. This study used the rhAmpSeq Vitis core panel haplotype markers to genotype 194 Muscadinia accessions from five cultivated populations and 15 wild populations collected across their native range. Wild populations from the western half of the native range were generally less genetically differentiated than hypothesized, but were genetically distinct from the material used in both past and present breeding efforts. One population collected from coastal North Carolina grouped closely with Vitis munsoniana accessions despite being well outside the reported range for that species. Principal coordinate and structure analyses revealed three main groups within the 194 accessions: one for cultivated material, one for wild V. rotundifolia, and one for V. munsoniana and V. popenoei. At K=5, structure results showed that more recent muscadine cultivars are further differentiated from wild accessions and varieties. These analyses confirmed our hypothesis that muscadine cultivars are genetically differentiated from their wild counterparts. This study also showed that genetic diversity in V. rotundifolia is not equally distributed across its native range and that the limited number of genotypes used in crop improvement efforts have not fully utilized the genetic diversity within the species.